Structural stability concepts in medieval and renaissance mechanics - Godoy, Luis Augusto (2011)
The identification of the origins of what we now call the theory of elastic stability is not an easy task. Most authors trace the origins to the pioneering work of Leonhard Euler in 1744, and some shift this origin to the experimental works of Petrus van Musschenbroek in 1729. However, other contemporary authors interested in the history of the discipline postulate that the works of Medieval and Renaissance scholars should be considered as the true sources of the buckling studies performed in the XVIII Century. This paper reports a historical research based on the original works of Al-Khazini, Jordanus de Nemore, Leonardo da Vinci, and Marini Merssene, in order to discuss what kind of knowledge they had about the topics of stability and lateral deflections of columns under axial loads. Our investigation shows that there were observations of the phenomenon considered, but those observations were not translated into a deeper understanding of the phenomenon, so that the causes of this effect or the role of strength on the response were not considered. Leonardo was closer than others in his understanding of the nature of the problem and produced some tentative rules of behavior; however, those were only documented in private writings and did not make an impact in his contemporaries or even 100 years later. We postulate that there was a continuity of problems between medieval authors and those who lived in the XVIII Century, rather than continuity in their concepts and approaches to solve those problems.